Collaboration Variability in Autism Spectrum Disorder - Blancas, Maria; Maffei, Giovanni; Sánchez-Fibla, Martí; Vouloutsi, Vasiliki; Verschure, Paul F. M. J. (Frontiers in Human Neuroscience, 2020)
This paper addresses how impairments in prediction in young adults with autism spectrum disorder relate to their behavior during a collaboration. To assess it, we developed a task where participants play in collaboration with a synthetic agent to maximize their score. The agent’s behavior changes during the different phases of the game, requiring participants to model their sensorimotor contingencies to play collaboratively. Our results (n = 30) show differences between autistic and neurotypical individuals in their behavioral adaptation to the other partner. Contrarily, there are no differences in the self-reports of that collaboration.